2017
DOI: 10.1016/j.hemonc.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic pemphigus as a presentation of acute myeloid leukemia

Abstract: Skin lesions are frequently encountered in clinical practice which can be a presentation of systemic diseases not excluding an occult malignancy. Commonly reported paraneoplastic dermatologic manifestations include acanthosis nigricans, dermatomyositis, erythroderma, hypertrophic osteoarthropathy, Sweet syndrome, and paraneoplastic pemphigus (PNP). PNP is a rare autoimmune mucocutaneous disease characterized by severe stomatitis, polymorphic skin eruptions, and associated underlying neoplasms most commonly non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Early intervention gave our patient a better outcome with an ongoing survival of 18months since diagnosis, maintaining complete remission. [4] Past studies have shown that, No significant variations of autoantibody levels with anti-Dsg1 in Pemphigus disease. [5] In pemphigus, autoantibodies form against desmoglein.…”
Section: Introductionmentioning
confidence: 99%
“…Early intervention gave our patient a better outcome with an ongoing survival of 18months since diagnosis, maintaining complete remission. [4] Past studies have shown that, No significant variations of autoantibody levels with anti-Dsg1 in Pemphigus disease. [5] In pemphigus, autoantibodies form against desmoglein.…”
Section: Introductionmentioning
confidence: 99%